Relationship between family support and diabetes mellitus medication compliance among elderly patients at Kartasura Public Health Center - Ayuninggar, Salsabila Chandra; Kartinah, Kartinah (Universitas 'Aisyiyah Yogyakarta, 2025)
Diabetes mellitus (DM) is a chronic disease with a high prevalence among the elderly and requires long-term management. Older adults with DM often face challenges such as cognitive decline, physical limitations, and comorbidities, which can hinder adherence to therapy, making family support a crucial factor influencing medication compliance. This study aimed to examine the relationship between family support and medication adherence among elderly patients with DM at the Kartasura Community Health Center. A quantitative method with a cross-sectional design and a simple random sampling technique was employed, involving 91 respondents selected based on inclusion and exclusion criteria. Research instruments included a family support questionnaire and a modified Hill-Bone questionnaire, which had been tested for validity and reliability in previous studies. The results showed that most respondents were aged 60–69 years, female, junior high school graduates, self-employed, married, and had lived with DM for 1–5 years. The majority received good family support (79.1%) and demonstrated high medication adherence (96.7%), and the Spearman test indicated a significant relationship between family support and medication adherence (p = 0.001). In conclusion, family support plays a vital role in improving medication compliance among elderly patients with DM; therefore, healthcare professionals are encouraged to actively involve families in diabetes care programs, provide education for caregivers, and develop community-based interventions that strengthen family engagement to enhance adherence and health outcomes in elderly populations.